Redeveloping depleted hydrocarbon wells in an enhanced geothermal system (EGS) for a university campus: Progress report of a real-asset-based feasibility study. (August 2018) - Weijermars, Ruud; Burnett, David; Claridge, David; Noynaert, Samuel; Pate, Mike; Westphal, Dan; Yu, Wei; Zuo, Lihua
Abstract: A feasibility study is being undertaken at Texas A&M University investigating the concept of using existing wellbores, formerly used for oil and gas production, to provide geothermal space conditioning for the 2000 acre Texas A&M RELLIS Campus. The RELLIS campus is currently constructing its first building and is expected to ultimately include approximately 2, 000, 000 ft 2 of education, research and office space. Several horizontal wellbores, originally used for hydrocarbon production, extending beneath the RELLIS campus are no longer economic and would otherwise be plugged and abandoned if an alternative use were not found. A conversion of such abandoned wellbores for multi-use geothermal energy supply (in a cascaded array of heating, cooling and electrical power generation) could substantially extend the reach of technically recoverable geothermal resources by paving the way for the implementation of a unique large-scale geothermal energy recovery project. This would be one of the first projects in the world to repurpose existing oil and gas wells for large-scale geothermal use. Much work remains to be done, but this progress report outlines the achievements of the initial assessment completed after the first year of the project study. Beyond providing clean energy, the RELLIS Campus geothermal initiative will help find solutions to the issues surrounding non-economic and abandoned oil and gas wellbores, which impact both oil and gas companies and the taxpayers. Highlights: Provide heating and cooling for a new 2 million square foot campus. First use of inactive hydrocarbon wells for this purpose. Develops technology leading to utilization of thousands of other inactive wells. Displaces conventional electricity and fuel use.